Answer:
Simplifying
3.2 = 2y
Solving
3.2 = 2y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-2y' to each side of the equation.
3.2 + -2y = 2y + -2y
Combine like terms: 2y + -2y = 0
3.2 + -2y = 0
Add '-3.2' to each side of the equation.
3.2 + -3.2 + -2y = 0 + -3.2
Combine like terms: 3.2 + -3.2 = 0.0
0.0 + -2y = 0 + -3.2
-2y = 0 + -3.2
Combine like terms: 0 + -3.2 = -3.2
-2y = -3.2
Divide each side by '-2'.
y = 1.6
Simplifying
y = 1.6
Explanation: